SARS-CoV-2 infection in immunocompromised patients: humoral versus cell-mediated immunity - Jianfeng Zhou; Meifang Han; Jianping Zhao; Jia Wei; Fankai Meng (Journal for ImmunoTherapy of Cancer)
Background The coronavirus disease 2019 (COVID-19) pandemic placed unprecedented pressure on various healthcare systems, including departments that use immunotherapies such as chimeric antigen receptor (CAR) T-cell therapy and immunosuppression therapy in organ transplantation units. The true impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on immunocompromised CAR T-cell therapy recipients and kidney transplant recipients (KTRs) has not yet been established.Case presentation In this report, we compare two patients with severe COVID-19 pneumonia in either the humoral or cell-mediated immunodeficient states. The first patient was a man in his early 30s who was diagnosed with refractory multiple myeloma. He received fully humanized, anti-B-cell maturation antigen, CAR T-cell therapy before 4 months and achieved strict complete remission. He was infected with SARS-CoV-2 starting on January 26, 2019 and gradually progressed to severe pneumonia. Throughout the clinical progression of the disease, SARS-CoV-2 could not be cleared due to his humoral immunodeficient state. During this period of his severe COVID-19 pneumonia, elevated cytotoxic T-cells were observed in this patient’s peripheral blood while elevated plasma levels of interleukin (IL)-2R, IL-6, tumor necrosis factor α, and ferritin were observed in his cytokine profiles. This patient eventually progressed into acute respiratory distress syndrome and recieved non-invasive ventilatory support. He failed to generate specific SARS-CoV-2 antibodies and died of respiratory failure on day 33 (d33). The second patient was a 52-year-old kidney transplant recipient (KTR) who took ciclosporin after renal transplantation for more than 7 years. He confirmed SARS-CoV-2 infection on January 20, 2019 and gradually progressed into severe pneumonia on d16 with a slightly elevated B-cell percentage and normal T-lymphocyte subsets. Viral clearance occurred together with the generation of specific anti-immunoglobulin G-SARS-CoV-2 antibodies after 2 weeks of treatment. He was symptom-free and discharged from the hospital on d42.Conclusion We report a CAR T-cell therapy recipient diagnosed with COVID-19 for the first time. His virus clearance failure and life-threating cytokine storm during SARS-CoV-2 infection suggested that any decision to proceed CAR T-cell therapy during COVID-19 pandemics will require extensive discussion of potential risks and benefits. Immunosuppressant treatment based on ciclosporin could be relatively safe for KTRs diagnosed with COVID-19.Trial registration number ChiCTR-OPN-1800018137.